Clients’ Satisfaction Assessment in Special Clinic at Bhumibol Adulyadej Hospital using SERVQUAL Model - KERDKAEW, CHATSURANG (Royal Thai Air Force Medical Gazette, 2022)
The purpose of this study was to assess Clients’ Satisfaction of Special Clinic at Bhumibol Adulyadej Hospital by using SERVQUAL Model. The sample group was composed of 400 of patients who sought treatment at the Special Clinic at Bhumibol Adulyadej Hospital, Bangkok. Data collection employed a Demographic Questionnaire and the adapted SERVQUAL Questionnaire. The data were analyzed by frequency, percentage, mean, standard deviation and paired t-test. According to the findings, the sample group was composed of females (71.5%) with aged over 60 years old (31%) and was entitled to medical treatment imbursement from Government or State Enterprise Officer (67%). Results show that patients reported higher average perception score than average expectation score indicating that patients do satisfy with service received (Mean = .03790 S.D = .038, t = 1.329, p = .185). Considering each dimension of service quality, patients reported higher perception score than expectation score with statistical significance in term of reliability, assurance, and empathy (p < .05). Based on the research findings, the researcher proposed that top management and personnel of Special Clinic at Bhumibol Adulyadej Hospital should develop to continues quality improvement.